Palladium-catalyzed direct C-H arylation of enamides with simple arenes - Pankajakshan, Sreekumar (2013)
Z only: An atom-economical synthetic route towards arylated Z-enamides through double CH functionalization is described. The Z/E selectivity of the palladium-catalyzed monoarylation is absolute (step A in scheme), and the molecular complexity of the products can be further endowed by a sequential second arylation, which requires the use of trifluoracetic acid (TFA; step B).